Overview of the Situation on Highly Pathogenic Avian Influenza Virus H5 in Russia in 2016–2017 - V. Yu. Marchenko; I. M. Susloparov; V. E. Ignat’ev; E. V. Gavrilova; R. A. Maksyutov; A. B. Ryzhikov (Проблемы особо опасных инфекций, 2018)
In 2016–2017, several outbreaks among wild and domestic birds caused by highly pathogenic influenza virus were recorded in the territory of the Russian Federation. After isolation of the highly pathogenic influenza A (H5N8) virus in the territory of the Republic of Tyva in May 2016, the virus was introduced into the west by wild birds, where it caused a massive epizootic. The death of agricultural poultry was noted in several regions of the European part of Russia and epizootics continued until the end of 2017. This paper presents the data on circulation of highly pathogenic influenza virus over the past two years. The current status regarding H5 influenza in the territory of the Russian Federation is also considered, where for the first time since 2005 a large-scale epizooty caused by the influenza virus subtype A (H5N8) was recorded. It is shown that the territory of Russia plays an important geographical role in the spread of influenza virus by wild birds from Southeast Asia to Europe and North America, and the research also suggests the possible continuation of circulation of highly pathogenic viruses in the territory of Russia.